Otomatisasi Penyediaan Data Gangguan DFR untuk Mempercepat Proses Identifikasi Gangguan Pada Sistem Ketenagalistrikan - Ivan Kusuma; Dwi Madya; Kiki Windasari (JURNAL ELEKTRO, 2025)
The analysis of power system conditions is crucial for effective management. Digital Fault Recorders (DFRs) provide vital data for analyzing disturbances. However, the speed of data retrieval from DFRs is often hindered by factors such as personnel expertise, application complexity, and communication channel readiness. To address this issue, PLN UIP2B has developed the Automatic DFR Data Retrieval Application (APDFR). This web-based, modular application utilizes reverse engineering to expedite the provision of disturbance recording data from various DFR brands. Performance analysis reveals that APDFR enables six-fold faster data retrieval compared to manual methods. By streamlining data retrieval, APDFR enhances the efficiency of disturbance identification in power systems, ultimately contributing to improved system reliability and resilience